2008
DOI: 10.1088/0022-3727/41/5/055403
|View full text |Cite
|
Sign up to set email alerts
|

Exciton spectra and energy band structure of CuGaSe2single crystals

Abstract: Photoreflectivity, wavelength modulation spectroscopy and photoluminescence measurements of CuGaSe2 are used to determine the exciton and band parameters as well as the energy band structure of CuGaSe2 at photon energies higher than the fundamental band gap. The spectral dependences of the real ε1 and imaginary ε2 components of the complex dielectric function ε(E) = ε1 (E) + iε2(E) are calculated using the Kramers–Kronig relations. As a result, the energy band structure of CuGaSe2 at photon energies higher tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 38 publications
4
25
0
Order By: Relevance
“…For Cu 3 MSe 4 there is an appre ciable enhancement of the calculated values by BSE in con trast to RBO in the visible and near ultra violet. The good absorption in the visible region of these materials compared to other ternary compounds containing Cu and Se, such as CuInSe 2 and CuGaSe 2 [44,45] makes them very promising semiconductors with applications in photocatalysis. Turning our attention to Cu 3 MS 4 , it is observed that Cu 3 VS 4 presents good absorption in the visible as well, with better values that some chalcopyrite compounds [44,45] but somewhat less than Cu 3 VSe 4 .…”
Section: Optical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…For Cu 3 MSe 4 there is an appre ciable enhancement of the calculated values by BSE in con trast to RBO in the visible and near ultra violet. The good absorption in the visible region of these materials compared to other ternary compounds containing Cu and Se, such as CuInSe 2 and CuGaSe 2 [44,45] makes them very promising semiconductors with applications in photocatalysis. Turning our attention to Cu 3 MS 4 , it is observed that Cu 3 VS 4 presents good absorption in the visible as well, with better values that some chalcopyrite compounds [44,45] but somewhat less than Cu 3 VSe 4 .…”
Section: Optical Propertiesmentioning
confidence: 99%
“…The good absorption in the visible region of these materials compared to other ternary compounds containing Cu and Se, such as CuInSe 2 and CuGaSe 2 [44,45] makes them very promising semiconductors with applications in photocatalysis. Turning our attention to Cu 3 MS 4 , it is observed that Cu 3 VS 4 presents good absorption in the visible as well, with better values that some chalcopyrite compounds [44,45] but somewhat less than Cu 3 VSe 4 . On the other hand, Cu 3 NbS 4 and Cu 3 TaS 4 absorb in the near ultra violet, with values that are bigger than CuInS 2 and CuGaS 2 .…”
Section: Optical Propertiesmentioning
confidence: 99%
“…Reshak and Auluck 17 employed the FP-LAPW method to calculate the electronic structure, linear and nonlinear optical susceptibilities, and birefringence of CuInX 2 (X = S, Se, Te) chalcopyrites. Levchenko et al 18 reported photoreflectivity, wavelength modulation spectroscopy, and photoluminescence measurements for determining the exciton band parameters and band structure of CuGaSe 2 at photon energies higher than the fundamental bandgap. Very recently, optical properties of Cu(In,Ga)Se 2 and Cu 2 ZnSn(S,Se) 4 were reported by Zhao and Persson.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the optical properties of a semiconductor are closely linked to its band structure, and even small changes in the band structure may cause a significant impact on optical properties. Before we proceed to present the detailed results, we first study which DFT method can reliably describe the linear optical responses of CuGaS 2 crystal that have been well studied experimentally. It should be pointed out that in the following sections, optical properties were calculated using the experimental band gaps shown in Table , namely, a scissor operator was employed to make the gaps obtained using different DFT methods match the same experimental result.…”
Section: Resultsmentioning
confidence: 99%
“…We aim at finding an efficient DFT approach to obtain sufficiently accurate optical properties of Cu-based chalcogenide materials, in which five common DFT methods used for the investigations of the electronic structures and physical properties of these compounds have been considered, including the PBE, PBE + U , hybrid HSE06, mBJ, ,, and mBJ + U methods . Using different theoretical approaches, we first particularly focus on ternary Cu-based semiconductors with the chalcopyrite structure whose linear optical susceptibilities have been well studied in experiments. After careful comparisons of the calculated results with experimentally measured optical constants, it indicates that the mBJ + U approach can yield optical properties in better agreement with experimental data than other DFT methods. Then, the linear and second-order NLO properties of other ternary and quaternary copper-based chalcogenide semiconductors are further explored using the mBJ + U method.…”
Section: Introductionmentioning
confidence: 99%